Pictures, perspectives, profiles: Reflections on interviews with critical adult educators - Andre P. Grace; Donovan Plumb (Adult Education Research Conference, 1995)
This paper reports on interviews we conducted with twenty critical adult educators from Europe and North America. While they express divergent opinions on a range of topics, these critical adult educators largely agree on several core themes in adult education.